2022
DOI: 10.1177/08861099221115721
|View full text |Cite
|
Sign up to set email alerts
|

When “Time Is Not Your Own”: Experiences of Mothering Students During the COVID-19 Pandemic

Abstract: As COVID-19 reached pandemic levels in March 2020, schools shifted to remote learning. Student parents in higher education had to adapt to their own remote learning and assume responsibility for childcare and their children’s education. Few studies have explored the impact of COVID-19 on mothers who are also full-time students. This study utilized a phenomenological approach to understand the lived experiences of mothering students during the COVID-19 pandemic. Student mothers were recruited from a large, publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Heightened vulnerabilities and an eroding capacity to withstand unrelenting changes and acceleration have occupied many pages of journals, including ours (Kim et al, 2021). Critical feminist research showed us how the pandemic disproportionately threatened the lives and well-being of Latinx immigrants (Cross & Gonzalez Benson, 2021), Latina immigrants (Cleaveland & Waslin, 2021), sex workers (Bromfield et al, 2021), intimate partner violence survivors (Heward-Belle et al, 2022), student mothers (LaBrenz et al, 2023), trafficking survivors (Namy et al, 2023), and anti-violence workers (Welch & Schwarz, 2023). Social work scholars like Stephanie Lechuga-Peña (2022) showed us how pandemic conditions disproportionately impacted the “productivity” of pre-tenure BIPOC junior women faculty.…”
mentioning
confidence: 99%
“…Heightened vulnerabilities and an eroding capacity to withstand unrelenting changes and acceleration have occupied many pages of journals, including ours (Kim et al, 2021). Critical feminist research showed us how the pandemic disproportionately threatened the lives and well-being of Latinx immigrants (Cross & Gonzalez Benson, 2021), Latina immigrants (Cleaveland & Waslin, 2021), sex workers (Bromfield et al, 2021), intimate partner violence survivors (Heward-Belle et al, 2022), student mothers (LaBrenz et al, 2023), trafficking survivors (Namy et al, 2023), and anti-violence workers (Welch & Schwarz, 2023). Social work scholars like Stephanie Lechuga-Peña (2022) showed us how pandemic conditions disproportionately impacted the “productivity” of pre-tenure BIPOC junior women faculty.…”
mentioning
confidence: 99%
“…As highlighted by hooks (1984), White womxn's experience as mothers has set the standard for motherhood and continues to do so. Even amidst research related to the COVID-19 pandemic and mothering (Batram-Zantvoort, et al, 2022;LaBrenz et al, 2022;Porter, 2021), the politics of "power, position and protection" of mothering is rarely centered unless by womxn of color (McClain, 2019, p. 3). This is also reflected in scholarship around MotherScholars and the COVID-19 pandemic (LeBlanc et al, 2022;Spradley et al, 2022), which posits that MotherScholars had similar experiences regardless of race or class.…”
mentioning
confidence: 99%